Introduction to management accounting - Horngren, Charles T., 1926- (Charles T. Horngren series in accounting, 2005)
Introduction to Management Accounting emphasizes decision-making throughout each chapter. Students develop a solid understanding of costs and cost behavior and the use of cost information for planning and control decisions, not just inventory valuation.